Focal Cortical Dysplasia Segmentation in 3D Magnetic Resonance Images of the Human Brain - Bergo, Felipe P. G.; Falcão, Alexandre X. (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC), 2009)
In this work we present an image processing pipeline for automatic segmentation of focal cortical dysplasia lesions in 3D magnetic resonance images of the human brain. Dysplasia lesions are a common cause of refractory epilepsy, especially in children, and their treatment often involve surgical intervention. To achieve this pipeline we developed several new image processing techniques, procedures and algorithms, which led to an automatic FCD segmentation method that is more accurate than the state-of-the-art and that, unlike the state-of-the-art, is applicable to MR images of children.